Commotio cordis without arrhythmic event and resuscitation: ECG, echocardiographic, angiographic and cardiovascular resonance imaging study - Maringhini, Giorgio (BMJ Case Rep, 2012)
We describe a case of commotio cordis in which the patient had an extensive cardiac evaluation, including ECGs, a coronary angiogram, a left ventriculogram, repeated echocardiography and cardiovascular MRI (CMRI). A healthy 17-year-old boy sustained an open-handed blow to the anterior part of the chest from a friend with whom he was playing. On admission ECG was performed that showed ST-T alterations and a TNI increase, with echocardiographic evidence of a localised pericardial effusion associated with a persistent myocardial blush at selective angiography. In addition, CMRI confirmed a local delayed enhancement in the same zone. An echocardiogram examination performed 30 days after discharge showed a complete disappearance of pericardial effusion and an improvement on ECG alterations. This is the first case report of a patient with commotio cordis, who did not show any arrhythmias and did not receive any resuscitation procedure, and was extensively studied by imaging methods.